A cross sectional study on tobacco usage among COVID 19 Positive patients admitted in a tertiary care centre in Mizoram India - Jane R Ralte; Lalrinawmi Hrahsel; Lalnuntluanga Sailo; Ganesh Shanmugasundaram Anusuya; Lalnunmawii Sailo; Lalrem Ruata (Asian Journal of Medical Sciences, 2023)
Background: Mizoram is one of the states in India with the high prevalence of tobacco usage both in terms of smoke form and smokeless form. In spite of high prevalence of smoking, the state has reported less COVID-19 related mortality. The prevalence of tobacco usage among the COVID-19 positive patients and its relation to clinical symptoms and mortality has not been studied in North East part of India.